2020
DOI: 10.1038/s41467-020-15416-4
|View full text |Cite|
|
Sign up to set email alerts
|

Atomically dispersed cobalt catalyst anchored on nitrogen-doped carbon nanosheets for lithium-oxygen batteries

Abstract: Developing single-site catalysts featuring maximum atom utilization efficiency is urgently desired to improve oxidation-reduction efficiency and cycling capability of lithium-oxygen batteries. Here, we report a green method to synthesize isolated cobalt atoms embedded ultrathin nitrogen-rich carbon as a dual-catalyst for lithium-oxygen batteries. The achieved electrode with maximized exposed atomic active sites is beneficial for tailoring formation/decomposition mechanisms of uniformly distributed nano-sized l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
220
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 275 publications
(239 citation statements)
references
References 78 publications
4
220
0
Order By: Relevance
“…However, in the case of the carbon obtained from chitosan, although the mesoporosity is lower, the capacity was the highest achieved. In this case, the effect of the presence of nitrogen clearly improves the performance of the material, as already described in the literature [ 31 , 32 , 33 , 34 ].…”
Section: Discussionsupporting
confidence: 77%
“…However, in the case of the carbon obtained from chitosan, although the mesoporosity is lower, the capacity was the highest achieved. In this case, the effect of the presence of nitrogen clearly improves the performance of the material, as already described in the literature [ 31 , 32 , 33 , 34 ].…”
Section: Discussionsupporting
confidence: 77%
“…Yan et al further found that Pt 2 dimers could also be deposited on graphene with ALD technology [86]. As shown in Figure 4( [89,102] could release metal atom vapor, which could be trapped by various substrates placed in the downstream and form corresponding SAECs. For example, Nb atom vapor released by arc discharge of Nb bulk could be trapped by carbon and formed the single-atom Nb-in-C catalyst [99].…”
Section: Vapor Deposition Methodsmentioning
confidence: 98%
“…Atom trapping method is a newly developed strategy to synthesize SAECs. At high temperatures, metal nanoparticles (Pt, Pd, Au, Rh, and Ni nanoparticles) [ 88 , 97 , 98 ], metal bulks (Pt net, Au foil, Pd bulk, Nb bulk, Cu foam, Co foam, and Ni foam) [ 99 101 ], metal oxides (Fe 2 O 3 , Co 2 O 3 , Cu 2 O, SnO 2 , and MoO 3 ) [ 87 ], and metal salts (CoCl 2 , H 2 PtCl 6 , H 2 PdCl 4 , HAuCl 4 , and H 2 IrCl 6 ) [ 89 , 102 ] could release metal atom vapor, which could be trapped by various substrates placed in the downstream and form corresponding SAECs. For example, Nb atom vapor released by arc discharge of Nb bulk could be trapped by carbon and formed the single-atom Nb-in-C catalyst [ 99 ].…”
Section: Synthetic Methods For Saecsmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 , 13 For example, Wang et al fabricated ultrathin carbon nanosheets by calcining ZIF-8 in an argon atmosphere. 14 The MOF-derived carbonaceous materials have flourished as advanced electrode materials in the energy storage field. 15 17 …”
Section: Introductionmentioning
confidence: 99%